1994
DOI: 10.1007/bf00678564
|View full text |Cite
|
Sign up to set email alerts
|

Complications in endoscopy of the lower gastrointestinal tract

Abstract: This is a report on 126 prospectively registered and controlled complications in 29,695 consecutive endoscopic procedures of the lower gastrointestinal tract. The overall complication rate is 0.4%. All endoscopic procedures were performed in our institution; no referrals "from other hospitals" are included. The therapy and prognosis of occurring complications are described. Especially after therapeutic endoscopy--above all, after polypectomy--the complication rate of 0.83% is not negligible. A serious aspect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(79 citation statements)
references
References 9 publications
4
62
0
13
Order By: Relevance
“…The current literature reports mortality rates of 0% to 50% [12]. The hospital mortality rate in the current study was 8.6%.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The current literature reports mortality rates of 0% to 50% [12]. The hospital mortality rate in the current study was 8.6%.…”
Section: Discussionsupporting
confidence: 42%
“…Colonic perforation resulting from colonoscopic and sigmoidoscopic procedures is a rare but serious complication with high rates of morbidity and mortality [1,3,6,7,12]. The frequency of perforations after colonoscopy is estimated to be 0.03% to 0.8% for diagnostic colonoscopy and 0.15% to 3% for therapeutic colonoscopy [22].…”
Section: Abstract: Colon Perforation -Colonoscopycomplication -Endosmentioning
confidence: 99%
“…For example, a study by the American Society for Gastrointestinal Endoscopy involving 25,000 diagnostic colonoscopies reported a complication rate of 0.35%. 4 In another large study, Jentscura et al 5 reported an overall complication rate of 0.4% in 26,695 prospectively registered colonoscopies. The most common complications in adult patients are hemorrhage, preparation-associated complications, adverse effects of sedative medicines, perforation, and bacteremia.…”
Section: Discussionmentioning
confidence: 97%
“…In this study 87% of the patients suffered from multiple organ diseases such as heart disease, encephalopathy, and nephrosis, and 24.3% of them had diseases in more than 3 vital organs, but the incidence of complication was significantly lower than that (0.4-1.4%) [29][30][31] with no occurrence of death and perforation [31] as a result of the improvement of intestinal canal preparation, simplification of colonoscopy intubation, and the appropriate measures taken for them according to the changes of their blood pressure and ECG when colonoscopy was performed. 29.2% of the patients in this study had a history of abdominal operation, but the successful rate of intubation was 98.9%.…”
Section: Discussionmentioning
confidence: 60%